Emerging and Re-emerging Vector-Borne Infectious Diseases and the Challenges for Control: A Review - Chala, Bayissa; Hamde, Feyissa (Frontiers in Public Health, 2021)
Vector-borne emerging and re-emerging diseases pose considerable public health problem worldwide. Some of these diseases are emerging and/or re-emerging at increasing rates and appeared in new regions in the past two decades. Studies emphasized that the interactions among pathogens, hosts, and the environment play a key role for the emergence or re-emergence of these diseases. Furthermore, social and demographic factors such as human population growth, urbanization, globalization, trade exchange and travel and close interactions with livestock have significantly been linked with the emergence and/or re-emergence of vector-borne diseases. Other studies emphasize the ongoing evolution of pathogens, proliferation of reservoir populations, and antimicrobial drug use to be the principal exacerbating forces for emergence and re-emergence of vector-borne infectious diseases. Still other studies equivocally claim that climate change has been associated with appearance and resurgence of vector-borne infectious diseases. Despite the fact that many important emerging and re-emerging vector-borne infectious diseases are becoming better controlled, our success in stopping the many new appearing and resurging vector-borne infectious diseases that may happen in the future seems to be uncertain. Hence, this paper reviews and synthesizes the existing literature to explore global patterns of emerging and re-emerging vector-borne infections and the challenges for their control. It also attempts to give insights to the epidemiological profile of major vector-borne diseases including Zika fever, dengue, West Nile fever, Crimean-Congo hemorrhagic fever, Chikungunya, Yellow fever, and Rift Valley fever.